Cardiovascular effects of chimeric antigen receptor t-cell therapy for refractory or relapsed non-hodgkin lymphoma. (25th November 2020) - Ganatra, S; Redd, R; Hayek, S; Parikh, R; Azam, T; Yanik, G; Spendley, L; Nikiforow, S; Jacobson, C; Nohria, A
Abstract: Purpose: Cardiovascular complications of chimeric antigen receptor T-cell (CAR T-cell) therapy are poorly understood. We examined the incidence, predictors and impact of new or worsening cardiomyopathy in patients undergoing CAR T-cell therapy. Methods: All patients with refractory or relapsed non-Hodgkin's lymphoma, undergoing CAR T-cell therapy at collaborative institutes underwent serial echocardiograms at baseline and within 7 days after developing high-grade cytokine release syndrome (CRS), and were followed for all-cause mortality. New or worsening cardiomyopathy was defined as a reduction in left ventricular ejection fraction (LVEF) >10% from baseline to <50% during the index hospitalization. Results: Among 187 consecutive CAR T-cell therapy patients, 116 (50 Grade ≤1 CRS, 66 Grade ≥2 CRS) had >1 echocardiogram performed and were included in this analysis. The median age was 63 (range 19–80) years, 42% were women, 91% were Caucasian. A total of 12 (10.3%) patients developed new or worsening cardiomyopathy with a decline in LVEF from 58±6% to 36±7% within a median of 12.5 (range 2–24) days of CAR T-cell infusion. In multivariable analyses, older age, prior stem cell transplantation, baseline angiotensin-converting enzyme inhibitor use and CRS grade ≥2 were associated with the development of cardiomyopathy. Patients who developed cardiomyopathy were more likely to require vasopressor support (p=0.004) and mechanical ventilation (p=0.014). LVEF improved in 9/12 (75%) patients. CAR T-cell associated cardiomyopathy did not impact overall mortality or cancer response to CAR-T cell therapy. Conclusions: Patients undergoing CAR T-cell therapy are at risk of developing cardiomyopathy and hemodynamic instability. Pre-CAR T-cell therapy cardiovascular risk stratification and echocardiogram surveillance during therapy should be considered for prompt identification and mitigation of cardiac complications. Funding Acknowledgement: Type of funding source: Private hospital(s). Main funding source(s): Anju Nohria, MD is supported by the Gelb Master Clinician Award at Brigham and Women's Hospital.